Unjuk Kerja Kolektor Surya dengan Absorber Bentuk V yang Dilengkapi Honeycomb dengan Beberapa Aspek Rasio - Ekadewi A. Handoyo; Niko Aris Sudiyanto; Prabowo Prabowo; Djatmiko Ichsani (Jurnal Teknik Mesin (Sinta 3), 2010)
A simple apparatus using solar radiation that is essential for people in tropical area like Indonesia is called solar collector. A solar collector can be applied to heat air which can be used to dry some crops or agricultural products. One of some effort to improve the solar collector performance is using a v-corrugated absorber plate or installing slats in a honeycomb shape over the absorber to reduce heat loss. This paper will describe the combination of both. From the research, it was found that a solar collector with v-corrugated absorber plate has its best performance when the velocity of air is 0.5 m/s with aspect ratio H/L = 3/1. The performance includes the collector efficiency and the increase temperature of air flowing through the collector.